Textual criticism and Dead Sea scrolls studies in honour of Julio Trebolle Barrera : florilegium complutense - Piquer Otero, Andres.; Torijano, Pablo A., 1968-; Trebolle Barrera, Julio C. (Supplements to the Journal for the Study of Judaism, 2012)
This volume includes papers on different topics of textual criticism of the Bible, history of the Hebrew text and the Septuagint, and Dead Sea Scrolls studies, contributed by friends and colleagues of Julio Trebolle Barrera to honour him on the occasion of his 65th birthday. The book presents a good selection of current research in the history and composition of the Bible, the Septuagint and the Dead Sea Scrolls, all with the aim of honouring a scholar who has excelled in those areas throughout his career.